Intellectual property and innovation - Ghosh, Shubha, 1964- (Edward Elgar Publishing, 2017)
This illuminating research review details leading articles on the theory and practice of intellectual property law as it applies to the promotion of innovation in economic, social, and legal dimensions. Topics include the role of law and incentives, cumulative and open forms of innovation, as well as discussion of its social dimensions, relationship with market institutions and how to chart a course for future innovation policy. This review offers a compelling overview of the ideas that ignite and enliven innovation scholarship, invaluable to academics and policymakers alike.